Development Of Sgoe Learning Model ( Stimulation, Guide, Observation, Evaluation ) In Junior High School Science Learning In Coffee Plantation Environment To Improve Problem Solving Skills - Farisi, M. Sodikin Al; Suratno, Suratno; Nuriman, Nuriman (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2024)
The purpose of this study is to describe the characteristics of SGOE learning model development (Stimulation, Guide, Observation, Evaluation) and determine the problem-solving ability of students in junior high school. The research method to be used in this study is the 4D method ( Define, Design, Develop, Disseminate). Trial design using LKPD Design. And the results of the effectiveness of the SGOE learning model show that it can improve students' problem-solving skills which is characterized by an increase in scores at meeting 1 obtained an average of 59% in the category of quite good. And at the 2nd meeting, an average score of 82% was obtained in the good category. SGOE learning model in students allows it to be developed more broadly with the development and problems and challenges faced by students in junior high schools around coffee plantations.